Auto-tuning Control Systems for Improved Operation of Continuous Fluidized Bed Spray Granulation Processes with External Product Classification. (2015) - Palis, Stefan; Dreyschultze, Christian; Neugebauer, Christoph; Kienle, Achim
Abstract: In this contribution control of continuous fluidized bed spray granulation processes with external product classification is studied. From a practical point of view control schemes being easy to implement and maintain using standard process control systems are preferable. Hence, the focus will be on standard PI control structures. In order to account for variations and uncertainties in the process an additional tuning procedure should be included. Here, an optimization based online controller adaptation scheme called iterative feedback tuning (ITF) will be investigated.